2010
DOI: 10.1038/sc.2009.177
|View full text |Cite
|
Sign up to set email alerts
|

Outcome parameters in spinal cord injury research: a systematic review using the International Classification of Functioning, Disability and Health (ICF) as a reference

Abstract: Objectives: This study is part of the development of an International Classification of Functioning, Disability and Health (ICF) Core Set for spinal cord injury (SCI). Its specific objectives were to identify outcome parameters reported in published studies on individuals with SCI in the early post-acute and chronic situation, and to identify and quantify the concepts of the reported parameters using the ICF as a reference. Methods: Electronic searches of Medline, EMBASE, PsycINFO and CINAHL from 2001 to 2005 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…7 However, a limitation of the described tool might be the fact that the WHO qualifiers has not yet been validated and there is no generally accepted, psychometrically sound measure of participation. 12 During the systematic evaluation, which was undertaken 6 months after introduction of this tool, 98 different inputs and feedbacks of patients and team were analysed and the required adaptations were transferred.…”
Section: Resultsmentioning
confidence: 99%
“…7 However, a limitation of the described tool might be the fact that the WHO qualifiers has not yet been validated and there is no generally accepted, psychometrically sound measure of participation. 12 During the systematic evaluation, which was undertaken 6 months after introduction of this tool, 98 different inputs and feedbacks of patients and team were analysed and the required adaptations were transferred.…”
Section: Resultsmentioning
confidence: 99%
“…5,19 The four questionnaires include the Short Form (SF36) 20 to address the concept of healthrelated quality of life, McGill Pain Questionnaire 21 to address pain and the Hospital Anxiety and Depression Scale 22 and Beck Depression Inventory 23 to address depression and anxiety (Table 3). Fourteen of the forty-six ICF categories (30%) of the WORQ-SELF were confirmed by the four questionnaires (Table 4).…”
Section: Worq-self and Standard Instrumentsmentioning
confidence: 99%
“…These instruments were identified based on the systematic reviews conducted in the context of the development of the ICF Core Sets of SCI 19 and VR 5 and have already been previously linked to the ICF. Contents of the instruments and the WORQ-SELF were compared.…”
Section: Comparison Of Assessment Measures Used In Vr and Sci With Thmentioning
confidence: 99%
“…12 A recent review that linked outcome measures to the ICF in people with SCI reported a large number of outcomes were related to 'Body Structures' and 'Body Functions' components. 13 This particular review evaluated a random sample of any study involving individuals with SCI without specifically addressing exercise interventions. Linking outcome measures from exercise intervention studies to the ICF is helpful, as it provides a knowledge base about which ICF categories, domains and components have been most frequently targeted, and which areas need to be addressed further in future studies.…”
Section: Introductionmentioning
confidence: 99%